Pengembangan Media Pembelajaran Matematika Berbasis Android untuk Tingkat SMP - Eka Septiyani; M Tohimin Apriyanto (Universitas Indraprasta PGRI, 2019)
This research is to develop android-based mathematics learning media for the junior high school level. This research was conducted at MTs Al-Wathoniyah 08. The research model used to develop this media was the ADDIE model. In this research, the product was tested on one media expert, one material expert, one linguist and a field trial. From the overall average value obtained from the validator, the expert teachers and students obtained a mean score of 3.65, which includes the category